Comparative study of active and inactive elderly persons through the assessment of activities of daily living and quality of life - S. Caporicci; M.F.O. Neto (Desafio Singular, 2011)
This study aimed at evaluating the activities of daily living and quality of active and inactive seniors' life. This is a descriptive research of a quantitative nature. Participants were 24 seniors, 12 physical activity practitioners (PPA) and 12 non-practitioners (NPPA). The instrument was a demographic questionnaire and SF-36 for measuring the quality of life and tests proposed by GDLAM. SPSS 15.0 was used for data analysis. The results obtained by the sociodemographic questionnaire for PPA and NPPA groups were, respectively: age − 69.5 and 70.0 years, marital status − 50.0% widower and 41.7% were married; education − 50.0% with complete elementary school and 58.3% with incomplete elementary school; health problems − 25.0% and 58.33% hypertension. In functional autonomy tests, the PPA group had shorter execution time when compared with the NPPA group; however, both groups found themselves in the rating of "weak" according to the protocol GDLAM. We concluded that there was no statistical difference between groups.